Towards a Higher Education System for Indigenous Students? Intercultural universities in Mexico - Gunther Dietz; Laura Selene Mateos Cortés (Universidade Federal do Rio Grande do Sul, 2022)
In Mexico, since 2003 an alternative university subsystem explicitly directed towards indigenous students has been emerging. In this article, we critically analyze these so-called "intercultural universities" as a new kind of higher education institution, through empirical research from different states of the art, from our own collaborative-ethnographic research project carried out in Veracruz and from annually organized, inter-institutional seminars on intercultural universities. Our analysis pinpoints shared tensions and contradictions, but also identifies different types of intercultural universities. We conclude with some recommendations for intercultural higher education policies in Mexico and Latin America.